Gli Stadi della società: lo stadio tra mutazioni sociali e culturali: Russo, P. (2021). Stadi di alterazione. Gli impianti sportivi di nuova generazione nel mutamento dei sistemi urbani. Firenze: Editpress. - Di Paola, Lorenzo (Eracle. Journal of Sport and Social Sciences, 2022)
This paper aims to examine the state of the art of social science studies about stadiums. The analysis of Russo’s book allows us to take stock of the latest developments in the sociology of sport to better understand how the stadium, understood as a cultural object, can help us to understand the economic and social evolution of urban systems. Finally, new avenues of investigation are proposed that can broaden the debate and give strength to a fertile and innovative field of study such as the sociology of sport.